Drain amylase aids detection of anastomotic leak after esophagectomy - Baker, Erin H.; Hill, Joshua S.; Reames, Mark K.; Symanowski, James; Hurley, Susie C.; Salo, Jonathan C. (Journal of Gastrointestinal Oncology; Vol 7, No 2 (April 01, 2016): Journal of Gastrointestinal Oncology, 2015)
Objective: Anastomotic leak following esophagectomy is associated with significant morbidity and mortality. As hospital length of stay decreases, the timely diagnosis of leak becomes more important. We evaluated CT esophagram, white blood count (WBC), and drain amylase levels in the early detection of anastomotic leak. Methods: The diagnostic performance of CT esophagram, drain amylase >800 IU/L, and WBC >12,000/μL within the first 10 days after surgery in predicting leak at any time after esophagectomy was calculated. Results: Anastomotic leak occurred in 13 patients (13%). CT esophagram performed within 10 days of surgery diagnosed six of these leaks with a sensitivity of 0.54. Elevation in drain amylase level within 10 days of surgery diagnosed anastomotic leak with a sensitivity of 0.38. When the CT esophagram and drain amylase were combined, the sensitivity rose to 0.69 with a specificity of 0.98. WBC elevation had a sensitivity of 0.92, with a specificity of 0.34. Among 30 patients with normal drain amylase and a normal WBC, one developed an anastomotic leak. Conclusions: Drain amylase adds to the sensitivity of CT esophagram in the early detection of anastomotic leak. Selected patients with normal drain amylase levels and normal WBC may be able to safely forgo CT esophagram.